Analysis of Delays in Construction Time of the Banjarsari Water Gate Project, Sidoarjo District Using Critical Path Method - Nopriyanto, Dwi Erry; Wulandari, Esti; Nugroho, Laksono Djoko (International Journal Labs, 2025)
The Banjarsari sluice gate, located on the Sidoarjo district's shipping river, faces various challenges that can affect its performance. These challenges include sedimentation, damage to building structures, and decreased water quality due to domestic and industrial waste. The implementation of the Banjarsari Water Gate maintenance project, especially the floor work, experienced seepage at the bottom of the water gate floor, resulting in structural failure of the water gate building. CPM method duration planning is a recommendation in choosing from the many methods available, because there is a calculation of the earliest time the project starts, the latest time the project begins, the earliest time completed, and the latest time completed, so that the time lag of all activities can be known. Analyze the acceleration of work duration by adding workers to the work on the critical path. The purpose of this research is to analyze the length of time required by the CPM (Critical Path Method) method for the work of the Banjarsari floodgate. In this study, the time analysis uses the CPM (Critical Path Method) method and is assisted by Microsoft Project 2021 Software. The analysis results obtained work through the critical path, namely demolition work and cyclope concrete casting, and obtained the results of the duration of work on the Banjarsari floodgate work after crashing to 66 working days from the initial duration of 72 working days.